2020
DOI: 10.1021/acschemneuro.0c00324
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nitric Oxide Production in Microglia with Novel Imidazodiazepines for Nonsedative Pain Treatment

Abstract: The goal of this research is the identification of new treatments for neuropathic pain. We characterized the GABAergic system of immortalized mouse and human microglia using electrophysiology and qRT-PCR. Cells from both species exhibited membrane current changes in response to γ-aminobutyric acid, with an EC 50 of 260 and 1940 nM, respectively. Human microglia expressed high levels of the γ-aminobutyric acid type A receptor (GABA A R) α 3 subunit, which can assemble with β 1 and γ 2 /δ subunits to form functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…It has been confirmed that the NE receptors exist on both astrocytes and microglia derived from the brain [ 11 , 12 ], and the SDH [ 13 ]. For example, NE inhibited microglia activation and cytokine expression in vitro [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the NE receptors exist on both astrocytes and microglia derived from the brain [ 11 , 12 ], and the SDH [ 13 ]. For example, NE inhibited microglia activation and cytokine expression in vitro [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly it is possible to simultaneously target inflammatory responses and impaired GABA-ergic signaling with molecules modulating the activity of GABA-A receptors . Both microglia and neurons express GABA-A receptors, and modulation of microglia activity via GABA-A receptors decreases secreting proinflammatory cytokines IL-6 and TNF-α. At the same time, modulation of neuronal GABA-A receptor activity might regulate the impaired GABA-signaling …”
Section: Introductionmentioning
confidence: 99%
“…In addition, astrocytes mediate neurotransmitter homeostasis through non-synaptic interactions such as uptake via GAT2 and GAT3 and metabolic conversion (Schousboe et al, 2013 ). Furthermore, with the exception of GAD, microglia also express ionotropic and metabotropic receptors as well as GABA-T (Kuhn et al, 2004 ; Lee et al, 2011 ; Nieman et al, 2020 ). However, the function of these receptors and transporters is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to astrocytes, microglia express the γ2-subunit (Höft et al, 2014 ; Nieman et al, 2020 ). It has been demonstrated that microglia actively survey and interact with synapses, extending their processes over the bulbous area of the synaptic buttons (Wake et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%